Literature Review Implementasi Bermain Peran untuk Perkembangan Kemampuan Sosial Emosional Anak di TK: Literature Review Implementation of Role Playing for the Development of Children's Social Emotional Ability in Kindergarten - Ashar Arif Paggama; A. Rezky Nurhidaya; Sadaruddin (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
Role-playing for early childhood is fun for students, so role-playing children need to pay attention to the interests and motivations of students. This study aims to analyze the implementation of role playing and describe the impact of emotional social development, this research was conducted using a literature review by collecting reference materials from various articles and journals based on the research objectives. The results of the literature review research related to the implementation of role playing while still requiring a foothold during role playing and paying attention to supporting factors by using the right media, educator creativity, teaching techniques and things that need to be anticipated by students' egocentrism and, undisciplined children and shy students. The impact of role playing obtained is courage, self-confidence, independence and communication as well as social interaction, and role playing has a significant influence on aspects of the development of social emotional skills of early childhood in kindergarten. Abstrak Bermain peran bagi anak usia dini merupakan hal yang menyenangkan bagi anak didik, sehingga anak bermain peran perlu memperhatikan minat dan motivasi anak didik. Penelitian ini memiliki tujuan untuk menganalisis implementasi bermain peran dan menggambarkan dampak perkemabangan social emosional, penelitian ini dilakukan dengan menggunakan literature review dengan cara mengumpulkan bahan referensi dari berbagai artikel maupun jurnal dengan berdasar dengan tujuan penelitian. Hasil penelitian literature review terkait implementasi bermain peran dengan tetap memerlukan pijakan selama bermain peran dan memperhatikan faktor pendukung dengan menggunakan media yang tepat, kreativitas pendidik, teknik mengajar serta hal yang perlu diantisipasi egosentrisme anak didik dan, anak yang belum disiplin serta anak didik yang pemalu. Dampak bermain peran didapatkan ialah keberanian, percaya diri, kemandirian dan komunikas serta interaksi social, dan bermain peran memiliki pengaruh signifikan terhadap aspek perkembangan keterampilan sosial emosional anak usia dini di TK.